Desain Pembelajaran Berbasis Web pada Mata Kuliah Pemrograman Visual - Lisnani .; Pradnyo Wijayanti; Sopian; Ira Irzawati (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
The visual programming course aims to transform mathematics learning through digital-based approaches by developing educational media applications and games. The primary objective of this research is to design and implement a web-based learning platform for the Visual Programming course, focusing on Scratch and MIT App Inventor materials. A design and development approach comprised needs analysis, design, development, implementation, and evaluation phases. The subjects of the implementation were 49 undergraduate students of the Mathematics Education Universitas Surabaya. Data collection methods included questionnaires and documentation. The results of this study are that the web-based learning design developed is beneficial for the learning process, as shown by a positive response, with more than 95% of respondents stating that they agree and strongly agree. The implications of this research suggest that the designed website can be utilized by a broader audience beyond students, due to its accessibility.